A mesoporous metal–organic framework based on a shape-persistent macrocycle. Issue 29 (12th March 2015) - Chen, Teng-Hao; Popov, Ilya; Chuang, Yu-Chun; Chen, Yu-Sheng; Miljanić, Ognjen Š.
Abstract : A mesoporous metal–organic framework (Zn-MCMOF ) with 86% void volume was synthesized from Zn atoms and a shape-persistent macrocyclic ligand based on a phenylene ethynylene scaffold. Upon activation, pores of theZn-MCMOF collapse, but are then regenerated through resolvation of crystals. Abstract : A mesoporous Zn-based metal–organic framework (MOF) was prepared from a shape-persistent phenylene ethynylene macrocycle functionalized with three –COOH groups. The rigid ligand has a ∼9 Å wide central cavity which serves as a predesigned pore. The macrocycles [π⋯π] stack into pairs, with their carboxylate groups connected via three Zn3 O14 C6 H2 clusters. The resulting MOF has a void volume of 86%.